2021
DOI: 10.1108/sr-05-2021-0150
|View full text |Cite
|
Sign up to set email alerts
|

Review on the wearable health-care monitoring system with robust motion artifacts reduction techniques

Abstract: Purpose Wearables are gaining prominence in the health-care industry and their use is growing. The elderly and other patients can use these wearables to monitor their vitals at home and have them sent to their doctors for feedback. Many studies are being conducted to improve wearable health-care monitoring systems to obtain clinically relevant diagnoses. The accuracy of this system is limited by several challenges, such as motion artifacts (MA), power line interference, false detection and acquiring vitals usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For instance, there is a preference for loose short sleeved T-shirts and a 69% acceptability rate for snug fitting garments but none of the participants want to wear tight fitting garments. From a technical viewpoint, a snug fit is a pre-requisite to obtain good quality signals during normal wear to minimise motion artifacts [30]. A tight fit would be required for sports activities that are more energetic and would cause major movement in the sensors' position during the activities, deteriorating signal quality.…”
Section: Survey Analysismentioning
confidence: 99%
“…For instance, there is a preference for loose short sleeved T-shirts and a 69% acceptability rate for snug fitting garments but none of the participants want to wear tight fitting garments. From a technical viewpoint, a snug fit is a pre-requisite to obtain good quality signals during normal wear to minimise motion artifacts [30]. A tight fit would be required for sports activities that are more energetic and would cause major movement in the sensors' position during the activities, deteriorating signal quality.…”
Section: Survey Analysismentioning
confidence: 99%
“…Each of these techniques has been presented and validated individually against reference systems. However, due to the complexity of the elbow joint, as well as numerous variables affecting measurement accuracy such as skin artefacts ( Cappello et al, 2005 ; Cutti et al, 2005 ; Prabakaran and Rufus, 2022 ), misalignment between externally observed and anatomical reference frames ( de Vries et al, 2010 ; Höglund et al, 2021 ) and sensor drift ( LaViola, 2003 ), defining the best type of calibration to adopt for every real-life scenario remains challenging. Additionally, when measuring with IMU, the type of movement performed and the anatomical joint axis considered further exacerbate differences in joint angle estimation across calibrations.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned noticeable interest in the PRV signal acquisition by wearable devices and its reliable processing to extract encoded information has prompted many research groups to sophisticated work on reducing artifacts in PPG. The vast majority of these studies has been summarized in recent review articles [12][13][14][15][16][17][18]. Overall, the approaches used fall into three general groups.…”
Section: Introductionmentioning
confidence: 99%